Atomic-scale structures determining the plasticity of metallic glasses viewed from the icosahedral medium-range orders and its spatial distribution - Kim, Hong-Kyu; Lee, Jae-Chul (Elsevier BV, 2024)
In the study of metallic glasses, the characterization of free volumes and icosahedral clusters has been a longstanding approach to understanding plasticity. However, recent research has illuminated the limitations of exclusively relying on these factors to explain the plastic deformation of metallic glasses. To address this limitation, we have introduced the concept called the h-value in a prior study, which quantifies the spatial distribution of disrupted interpenetrating connections of icosahedra and provides insights into how minor elements influence the deformation behavior of metallic glasses. However, the h-value was only employed on Cu50Zr50, Cu47.5Zr47.5Al5, and (Cu0.5Zr0.5)100-xAgx alloys and provided insight into the correlation between the spatial distribution of icosahedra and plasticity, but it is needed to be validated on a wider range of alloys to confirm the applicability of the h-value. In this study, we utilize a Cu？Zr binary amorphous system, known for its compositional diversity and corresponding wide range of plasticity, to validate and benchmark our approach against experimental results. Our findings underscore the robustness of the h-value as a structural descriptor, representing the degree of spatial distribution within the local structural basis. This metric holds promise as a valuable tool for determining the plasticity of metallic glasses.